2017
DOI: 10.1103/physrevlett.119.161101
|View full text |Cite
|
Sign up to set email alerts
|

GW170817: Observation of Gravitational Waves from a Binary Neutron Star Inspiral

Abstract: Gravitationswellen -ein leichtes Zittern der raumzeitVor 1,3 Milliarden Jahren: Seit langer Zeit schon haben sich in einer fernen Galaxie zwei schwarze Löcher umkreist, Gebilde von so ungeheurer Dichte, das selbst Licht ihrer Schwerkraft nicht mehr entweichen kann und von ihnen eingefangen wird. Seit Jahrmillionen haben sie bei ihrem Tanz umeinander mit ihrer masse die Raumzeit verformt und dabei Gravitationswellen abgestrahlt. ihr Abstand wurde dabei immer kleiner, ihre Geschwindigkeit immer höher, bis sie sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

244
6,671
8
33

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8,465 publications
(7,166 citation statements)
references
References 277 publications
244
6,671
8
33
Order By: Relevance
“…The alert for GW170817 was issued 40 minutes after the trigger, on 2017 August 17 at 13:21 UT (Abbott et al 2017; LIGO Scientific Collaboration & Virgo Collaboration 2017b), and was promptly received by our automated GCN listener system. Two subsequent GCN circulars indicated that the highsignificance candidate was consistent with a binary neutron star merger at » d 40 Mpc and coincident within 2 s with a short The entire GW localization region was visible from Chile at the beginning of the night, setting within the first ∼1.5 hr.…”
Section: Decam Counterpart Searchmentioning
confidence: 99%
“…The alert for GW170817 was issued 40 minutes after the trigger, on 2017 August 17 at 13:21 UT (Abbott et al 2017; LIGO Scientific Collaboration & Virgo Collaboration 2017b), and was promptly received by our automated GCN listener system. Two subsequent GCN circulars indicated that the highsignificance candidate was consistent with a binary neutron star merger at » d 40 Mpc and coincident within 2 s with a short The entire GW localization region was visible from Chile at the beginning of the night, setting within the first ∼1.5 hr.…”
Section: Decam Counterpart Searchmentioning
confidence: 99%
“…Since the observation of GW170817 and GRB 170817A [5,43,44], many alternative theories of gravity have been highly constrained by the speed bound of the GW [45],…”
Section: Gravitational Wave Polarizations In Horndeski Theorymentioning
confidence: 99%
“…Finally, let us mention that Einstein-aether theory is highly constrained by various experimental observations, especially the speed bound derived from GW170817 and GRB 170817A [5,[43][44][45]. Apart from this speed bound and the absence of the gravitational Cherenkov radiation, there are constraints from the observations of pulsars (such as the post-Newtonian parameters, |α 1 | < 4 × 10 −5 [65] and |α 2 | < 2 × 10 −9 [66,67] …”
Section: Einstein-aether Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The burst is highly noticeable due to its connection to the gravitational wave (GW) GW170817, detected by Laser Interferometer Gravitational-wave Observatory (LIGO) and Virgo, approximately 1.7s before the GBM triggered (Abbott & et al 2017). All the physical quantities of this object is crucial for understanding the event.…”
mentioning
confidence: 99%